Pengaruh Flypaper Effect Pada Dana Alokasi Umum dan Pendapatan Asli Daerah Terhadap Belanja Daerah Provinsi Lampung Tahun 2016-2019 dalam Perspektif Ekonomi Islam - Herlina Kurniati; Yulistia Devi (JES (Jurnal Ekonomi Syariah), 2022)
Many Regionals Government in Indonesia still rely on DAU allocations to finance regional expenditures and development without optimizing the potential of the regions. When DAU allocation obtained is large, the regions will try to keep DAU in the next period at the nominal value. PAD is able to finance local government at a maximum of 20%. This fact has led to asymmetrical behavior in local government. The regional government responds to the transfer of funds in the form of balancing funds, especially DAU which is realized in the regional budget. As regional spending is greater than the transfer, it is called the flypaper effect. The method used in this research is descriptive quantitative analysis method using panel data regression. The data analysis with regression uses the Eviews 9.0 program. The data used in this research use panel data with independent variables, namely General Allocation Fund (DAU) and Regional Original Revenue (PAD). The dependent variable is Regional Expenditure. The results of this study are: 1) General Allocation Funds have no effect on Regional Expenditures; 2) Regional Original Revenues affects Regional Expenditures; 3) General Allocation Funds and Regional Original Revenues simultaneously affect Regional Expenditures; 4) There is no Flypaper Effect in Regency/City Government of Lampung Province 2016-2019; 5) Regional Expenditures of Lampung Province is not compatible with the Islamic economic perspective.